(untitled) (Third Sector Social Economic Review, 2023)
The development of the Electronical Warehouse Receipt (EWR) market in Turkey began when the commodity exchanges initially authorised were traded on electronic platforms. This process has gained momentum after the Konya Commodity Exchange established the EWR trading market in BorsaKonya. The importance and magnitude of the EWR market is underlined by the fact that Turkish Mercantile Exchange is established with a national exchange status and its progress towards becoming an international mercantile exchange. The focus of this study is on the performance of the EWR market year-by-year performance development and the performance of the intermediary institutions that serve as settlement members in the EWR market. The NMD, CRITIC, and Entropy methods were used to weight criteria, the Bayesian method was used to integrate the calculated weight values, and the MABAC method used to evaluate alternatives. The working criteria include the number of producers and investors who perform active transactions in the EWR market, the number of licenced warehouses where EWR transactions are performed, the number of brokerage houses that provide clearing, settlement and custody services, total licenced capacity, the total number of transactions performed, total trading volume, total number of transactions and the total EWR balances stored at the end of the year. In terms of EWR market performance, it was found that the best performances were in the ranking results of Entropy-MABAC, CRITIC-MABAC, NMD-MABAC and Bayes-MABAC methods in 2022 and 2021. In addition, the first two clearing member intermediaries to have the most successful performance according to 2018-2021 period data were Ziraat Bank and Deniz Bank.